Comparing the Efficacy of Triamcinolone Acetonide Iontophoresis versus Topical Calcipotriol/Betamethasone Dipropionate in Treating Nail Psoriasis: A Bilateral Controlled Clinical Trial - Nasrin Saki; Shahla Hosseinpoor; Alireza Heiran; Ali Mohammadi; Mehdi Zeraatpishe (Hindawi Limited, 2018)
Background and Objective. Psoriasis is a common chronic inflammatory skin disorder affecting any age and gender. The clinical presentation of the nail disease depends on the location of the pathology: nail bed or nail matrix. We aimed to compare the therapeutic effects of triamcinolone acetonide iontophoresis (TI) and topical calcipotriol/betamethasone dipropionate in the nail bed and nail matrix involvements of psoriasis using Nail Psoriasis Severity Index (NAPSI). Materials and Methods. In the present bilateral comparison clinical trial, sixteen patients with clinical diagnosis of nail psoriasis were enrolled and randomized to receive six monthly TI treatment sessions either on their right or on the left hand target nails and daily application of topical calcipotriol/betamethasone dipropionate for six months on their other hand. Clinical efficacy was evaluated according to target nails NAPSI before and after the treatment. Wilcoxon sign-rank test and repeated measures ANOVA were used to compare the efficacy of the treatments. Results. The results did not show any difference between the therapeutic effects of TI and topical calcipotriol/betamethasone dipropionate regarding the nail bed score (P value =  .356), matrix score (P value =  .137), and total NAPSI (P-value =  .098). Conclusion. Monthly TI has an equal efficacy compared to daily topical calcipotriol/betamethasone dipropionate. It can be used as a safe, easy, and compliant treatment for nail psoriasis. This study is registered under IRCT2017050233778N1.